Pendampingan LMS Berbasis Outcome-Based Education dan Conditional Access pada Dosen PGSD Universitas Hamzanwadi - Hirmayanti; Harianto; Zaenul Amri (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
The advancement of digital technology in higher education has encouraged the utilization of Learning Management Systems (LMS) not only as platforms for delivering learning materials but also as tools for supporting competency-based and adaptive learning. However, LMS implementation in the Elementary School Teacher Education Program at Hamzanwadi University has primarily focused on basic learning features and has not fully utilized adaptive learning functionalities such as conditional access. This community service program aimed to enhance lecturers’ competencies in developing and managing an Outcome-Based Education LMS integrated with conditional access features to support adaptive learning. The program was conducted through several stages, including needs assessment, training material development, workshops, digital course design practices, LMS implementation mentoring, and activity evaluation. The results indicated that all participants successfully developed Outcome-Based Education courses within the LMS, while 15 lecturers successfully implemented the conditional access feature in their courses. In addition, 85% of participants reported that the mentoring activities improved their ability to develop digital assessments, design adaptive learning activities, and utilize LMS features more effectively. The implementation of the Outcome-Based Education LMS also facilitated more systematic and measurable monitoring of student learning outcomes. Therefore, the mentoring program contributed positively to strengthening lecturers’ digital competencies and supporting the development of adaptive learning environments oriented toward student learning outcomes